2022
DOI: 10.3389/fimmu.2022.940562
|View full text |Cite
|
Sign up to set email alerts
|

Facing the Omicron variant—how well do vaccines protect against mild and severe COVID-19? Third interim analysis of a living systematic review

Abstract: BackgroundThe severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) Omicron variant is currently the dominant variant globally. This third interim analysis of a living systematic review summarizes evidence on the effectiveness of the coronavirus disease 2019 (COVID-19) vaccine (vaccine effectiveness, VE) and duration of protection against Omicron.MethodsWe systematically searched literature on COVID-19 for controlled studies, evaluating the effectiveness of COVID-19 vaccines approved in the European Uni… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
25
0
3

Year Published

2022
2022
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(33 citation statements)
references
References 49 publications
5
25
0
3
Order By: Relevance
“…In the analysis of our data from the Delta wave VE was higher for two doses (89%, 95% CI: 84-92%) and three doses (97%, 95% CI 95-99%). The results from the Omicron wave analyses were comparable with the results of other studies and systematic reviews [21][22][23][24][25].…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…In the analysis of our data from the Delta wave VE was higher for two doses (89%, 95% CI: 84-92%) and three doses (97%, 95% CI 95-99%). The results from the Omicron wave analyses were comparable with the results of other studies and systematic reviews [21][22][23][24][25].…”
Section: Discussionsupporting
confidence: 85%
“…Our analysis revealed stable protection up to one year (for three vaccine doses). As other studies showed that protection against symptomatic infection decreases noticeably with increasing time lag after the last vaccination dose [22, 23, 25-27], this is an important finding.…”
Section: Discussionsupporting
confidence: 60%
“…Yu et al also found that the pooled proportion of asymptomatic infection and non-severe disease with Omicron were 25.5% and 97.9%, respectively, which is significantly higher than those of Delta with 8.4% and 91.4% [ 14 ]. The vaccination of a booster dose that may cause variants had less effect on the severity of COVID-19 or long COVID-19 when compared with the epidemic of the wild-type strain or the Alpha variant [ 73 , 74 , 75 , 76 ].…”
Section: Discussionmentioning
confidence: 99%
“…Lower VE for Omicron was confirmed by many subsequent studies; moreover, further evidence suggested that there was rapid waning of protection against infection and symptomatic disease due to Omicron. [7] , [8] …”
Section: Introduction Background and Meeting Objectivesmentioning
confidence: 99%